Issues and challenges of reclaimed water usage: a case study of the dragon-shaped river in the Beijing Olympic Park. Issue 4 (19th May 2017) - Zhou, Xiaoqin; Li, Zifu; Staddon, Chad; Wu, Xuejun; Song, Han
ABSTRACT: Increased use of reclaimed water could be one of the solutions to Beijing's growing water shortage, particularly for non-potable (e.g. landscaping) purposes. The dragon-shaped river, a large artificial waterscape built on the site of the 2008 Beijing Olympic games, offers a useful case study of the issues and challenges attendant on wastewater reclamation and reuse. Of particular interest is the use of phytoremediation techniques for bioremediation of nutrient loads. This article presents the results of ongoing monitoring which indicate that phytoremediation is succeeding in preventing eutrophication, though some challenges, notably management of aquatic biomass, remain.